Jeersannidhi Award Lecture - Pathogen diversity and plant disease management - R.P. THAKUR, R.P. THAKUR (Indian Phytopathology, 2002)
The importance of protecting the biodiversity of plant pathogenic fungi is discussed, with a view to the management of genetic diversity for host plant resistance.